Debt determinants of shari’ah approved firms: Empirical evidence from Malaysia - Ramli, Nurshamimitul Ezza; Haron, Razali (IIUM Press, 2017)
The issue of high reliance on debt has raised major concern especially since its impact has been linked to the several corporate problems in United States’ big corporations such as Enron and Lehman Brothers. On a wider scope, the impact of debt may also be evidenced by the Greek Depression in the year 2009. Various studies have been conducted to explain which factors determine debt of the firms, given different setting of periods, countries and methodologies. Uniquely, this study focuses on the firms which stocks are Shari’ah approved in accordance to the Malaysia’s Securities Commission guidelines. This study covers a balanced panel of 239 Shariah approved firms listed on the Bursa Malaysia for the period of analysis from 2000 to 2014. To meet its objective, this study employs a static panel regression model which includes the pooled OLS, random effect model (REM) and fixed effect model (FEM). The study also conducts a robustness test to the empirical model. Several factors have been examined and the result shows that certain firm-specific variables like growth opportunity, size, bankruptcy risk, non-debt tax shield (NDTS) and Herfindahl-Hirschman Index are significant determinants of a firm’s debt. Also macro variables such as inflation, GDP and economic crisis are also found to be significant determinants of Shariah approved firms’ debt. In contrast with the prior studies that focuses on the non-Shariah approved firms, the output from this study provides new insight and understanding on the debt determinants of Shariah approved firms.